Miswak Starch-based Gel As Topical Preparation For Potential Management Of Infective Ulceration - Nadia Halib; Rohazila Mohamad Hanafiah; Izzah Syahirah Ahmad Azam; Mohd Ikram Mohd Shamshuddin; John Chong Keat Hon (JK Welfare & Pharmascope Foundation, 2024)
Non-Indexed Publication